Akuntabilitas, Partisipasi Masyarakat dan Transparansi dalam Pengelolaan Dana Desa (Studi Kasus Pada Desa Tamannyeleng, Kecamatan Barombong, Kabupaten Gowa) - Sri Rahayu Syah; Sufardi Sufardi; Sulaeha Sulaeha (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2022)
This research aims to determine accountability, community participation and transparency in the management of village funds in Tamannyeleng Village, Barombong District, Gowa Regency. The data of this research were obtained from administrative and financial data of Tamannyeleng Village, interviews with village officials and community representatives. This study uses a qualitative method with a descriptive approach. The results of the research with the title Accountability, Community Participation and Transparency in the Management of Village Funds in Tamannyeleng Village, Barombong District, Gowa Regency are that the role of accountability and community participation has been carried out well, as seen from the accountability report of the Village Head as the village fund manager is complete and the community has been involved in planning, implementation, supervision of village fund management. Publication of village fund management in the form of banners already exists, but reports on the realization of village funds are still difficult to access. So the transparency is not yet fully transparent. Keywords: Accountability, community participation, Transparency and Village Fund Management Penelitian ini bertujuan untuk mengetahui akuntabilitas, partisipasi masyarakat dan transparansi dalam pengelolaan dana desa pada Desa Tamannyeleng Kecamatan Barombong Kabupaten Gowa. Data penelitian ini diperoleh dari data-data administrasi dan keuangan Desa Tamannyeleng, wawancara dengan aparat desa dan perwakilan masyarakat. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Hasil penelitian Hasil penelitian dengan judul Akuntabilitas, Partisipasi Masyarakat dan Transparansi Dalam Pengelolaan Dana Desa Pada Desa Tamannyeleng Kecamatan Barombong Kabupaten Gowa adalah Peran akuntabilitas dan partisipasi masyarakat telah terlaksana dengan baik dilihat dari laporan pertanggungjawaban Kepala Desa selaku pengelola dana desa sudah lengkap dan masyarakat telah terlibat dalam perencanaan, pelaksanaan, pengawasan pengelolaan dana desa. Publikasi pengelolaan dana desa dalam bentuk spanduk sudah ada namun untuk laporan realisasi dana desa masih sulit untuk diakses. Jadi untuk transparansinya belum sepenuhnya transparan. Keywords: Akuntabilitas, Partisipasi Masyarakat, Transparansi dan Pengelolaan Dana Desa